DETERMINAN AKUNTABILITAS KEUANGAN DESA PADA MASA PANDEMI COVID-19 - Sahala Purba; Septony Benyamin Siahaan; Farida Sagala; Rahel Junita; Tonida Charles Duha (Ultimaccounting Jurnal Ilmu Akuntansi, 2022)
Abstract— This research aims to determine and analyze the impact of the internal control system, human resource capacity, inspection, and apparatus skills on village financial accountability in villages in Siempat Nempu Hulu District, Dairi Regency. This type of research is causal associative research and uses primary data. The data collection method used is a questionnaire. The study method used in this research is descriptive analysis and multiple linear regression. This research was conducted in 12 villages in Siempat Nempu Hulu Subdistrict, Dairi Regency, and each village had 3 respondents, namely the head of the village government, the village secretary and the head of finance, so that the number of respondents was 36 people. This research was conducted in April - May 2021. The results of this research show that the internal control system, Human Resource Capacity and apparatus skills have a positive and significant impact, while the audit has a negative impact on village financial accountability in villages in Siempat Nempu Hulu District, Dairi Regency. Keywords: Internal Control System; Human Resource Capacity; Examination; Apparatus Skills; And Village Financial Accountability